The Circulating Anticoagulant in Disseminated Lupus Erythematosus - Perkins, Herbert A.; Acra, D. J (Thrombosis and Haemostasis, 1961)
The circulating anticoagulant in a case of lupus erythematosus was demonstrated to accelerate the disappearance of formed thromboplastin. We were unable to show that it acted against any single blood coagulation factor. We suggest that its action may be entirely explained on the basis of destruction of the final prothrombin converting factor, with and without the presence of tissue thromboplastin. This hypothesis still leaves no explanation for the consistently low levels of prothrombin in this condition.